Feasibility, acceptability, and effectiveness of school-based dance movement psychotherapy for children with emotional and behavioral difficulties - Moula, Zoe; Powell, Joanne; Brocklehurst, Shirley; Karkou, Vicky (Frontiers in Psychology, 2022)
Background: Schools have been increasingly employing dance movement psychotherapists to support children cope with daily worries and stress, express and understand their emotions, develop self-awareness and self-esteem. However, evidence on the impact of dance movement psychotherapy as a tool for prevention of mental health difficulties in childhood remains limited. Methods: Sixteen children (aged 7-9) with mild emotional and behavioural difficulties from two primary schools were randomly assigned to a Dance Movement Psychotherapy (DMP) intervention or to a waiting list, within a larger pilot cross-over randomized controlled study which aimed to a) test whether all elements of study design can work together and run smoothly in a full-scale RCT; and b) investigate the effectiveness of arts therapies in improving children’s health related quality of life (HRQOL; EQ-5D-Y), wellbeing and life functioning (Child Outcome Rating Scale; CORS), emotional and behavioural difficulties (Strengths and Difficulties Questionnaire; SDQ), and duration of sleep (Fitbits). The therapeutic process was also evaluated through interviews with children, participant observations, the Children’s Session Rating Scale (CSRS), and ratings of adherence to the therapeutic protocol. Results: The findings indicated that DMP led to improvements in children’s life functioning, wellbeing, duration of sleep, emotional and behavioural difficulties, but not in quality of life. The improvements were maintained at the follow-up stages, up to six months post-intervention. Interviews with children also suggested positive outcomes, such as self-expression; emotional regulation; mastery and acceptance of emotions; improved self-confidence and self-esteem; reduced stress; and development of positive relationships. However, children would have preferred smaller groups and longer sessions. Conclusions: This study indicated that all outcome measures would be suitable for inclusion in a larger randomized controlled trial, though the EQ-5D-Y is not recommended as a stand-alone measure due to its lack of sensitivity and specificity for young participants. The adherence to the therapeutic protocol ratings differed between children and adults, highlighting the need to include children’s voice in future research. Strategies are also proposed of how to conduct randomisation of participants in ways that do not hinder the therapeutic process.